2021
DOI: 10.1093/jpp/rgab172
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between curcumin and curcumin nanoemulsion on high-fat, high-fructose diet-induced impaired spermatogenesis in rats

Abstract: Objectives Curcumin is a promising nutraceutical with reported diverse therapeutic properties, but of limited oral bioavailability. The current manuscript investigates the role of encapsulation of curcumin in nanoemulsion form in counteracting the adverse effect of chronic ingestion of a high-fat high-fructose diet (HFHF) by juvenile male rats regarding testicular abnormalities and declined spermatogenesis. Methods Curcumin n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…It was also demonstrated that CUR nanoparticles at a dose of 15 mg/kg in rats counteracted nano-hydroxyapatite-induced decreased testicular oxidative stress and 8-OHDG level (Yousef et al, 2021). Moreover, previously published results by our group demonstrated that CUR in its conventional form, as well as the nanoemulsion form at the same dose levels ranging from 2.5 to 10 mg/kg exhibited antioxidant and anti-inflammatory effects, preserved cellular energy represented by the AEC ratio, and lowered 8-OHdG level in other animal models (Ahmed-Farid et al, 2017;Nasr et al, 2022).…”
Section: Ta B L E 1 Effect Of Different Treatments On Serum and Hepat...mentioning
confidence: 84%
See 4 more Smart Citations
“…It was also demonstrated that CUR nanoparticles at a dose of 15 mg/kg in rats counteracted nano-hydroxyapatite-induced decreased testicular oxidative stress and 8-OHDG level (Yousef et al, 2021). Moreover, previously published results by our group demonstrated that CUR in its conventional form, as well as the nanoemulsion form at the same dose levels ranging from 2.5 to 10 mg/kg exhibited antioxidant and anti-inflammatory effects, preserved cellular energy represented by the AEC ratio, and lowered 8-OHdG level in other animal models (Ahmed-Farid et al, 2017;Nasr et al, 2022).…”
Section: Ta B L E 1 Effect Of Different Treatments On Serum and Hepat...mentioning
confidence: 84%
“…Curcumin (CUR), a component of Curcuma longa, is a polyphenolic compound that has long been reputed for its anti‐inflammatory, anti‐oxidative, and anti‐hyperlipidemic potentials (Ahmed‐Farid et al, 2017; Azhdari et al, 2019; Manzoni et al, 2019; Nasr et al, 2022). Growing evidence has delineated that CUR can regulate different signaling molecules to retard the progression and development of atherosclerosis (Li et al, 2020; Momtazi‐Borojeni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations